Changes of electron density and defects distribution in binary and ternary iron alloys studied by positron annihilation - Udovsky A.; Grafutin V.; Kolotushkin V.; Miloserdin V.; Evstukhina I.; Mischenko A.; Ermakov V.; Samosadny V.; Funtikov Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Properties of binary and ternary iron based alloys doped by different additions were investigated. It was shown for binary alloys containing chromium, molybdenum and tungsten were that results of doping by 0.8% molybdenum and tungsten are similar to those for the sample doped by 9%chromium. Ternary alloys containing chromium and less amounts of molybdenum, tungsten and vanadium were investigated as well. Two types of defects were observed: divacancies and cluster-like defects. It was shown that the electron density in ternary alloys is similar to that in binary alloys containing 0.8% molybdenum.